Moral and ethical practice in organizations - Wookey, Charles (Henry Stewart Talks, 2020)
Blueprint for Better Business, Purpose, Executive team, Board of directors, Neoclassical economic system, Profitability, Society, Shareholder value, Moral dilemmas, Corporate culture, Whistleblowing, Psychological safety, Ethics at work, Pricing, Airline industry, Tobacco industry